Becoming a digital parent a practical guide to help families navigate technology - Rogers-Whitehead, Carrie, 1983- (New York, NY : Routledge, 2021)
Becoming a Digital Parent is a practical, readable guide that will help all parents have confidence to successfully navigate technology with their children. It accessibly presents evidence-based guidance to offer an overview of the digital landscape, empowering parents to embrace opportunities whilst keeping children responsible and safe online. Covering a range of topics including developmental stages, screen time, bed time, gaming, digital identities, and helpful parenting apps and resources, Carrie Rogers-Whitehead explores the challenges and opportunities involved in parenting in the digital age. With advice for parents of babies through to teenagers, each chapter includes an explanation of the latest research, interviews with parents and experts, and helpful case studies gathered by the author during her extensive experience of working directly with parents and children. This book will show parents how to communicate better with their children, create a family technology plan, put in place intervention strategies when things happen, and take advantage of the benefits technology can afford us. Becoming a Digital Parent is ideal for all parents looking to effectively navigate the technological world, and the range of professionals who work with them.
OCLC-licensed vendor bibliographic record.
Keywords: Parenting; Technology and children; Internet and children; Digital media -- Social aspects; PSYCHOLOGY / Developmental / Child; PSYCHOLOGY / Developmental / General